Primary Neuroendocrine Tumor of the Orbit Presenting With Acute Proptosis. Issue 1 (January 2018) - Thyparampil, Preeti J.; Yen, Michael T.; Dhingra, Sadhna; Shetlar, Debra J.; Zarrin-Khameh, Neda; Musher, Benjamin L.
Abstract : Primary neuroendocrine tumors of the orbit are exceedingly rare and typically present with gradual, progressive exophthalmos. In this report, an otherwise healthy 64-year-old woman undergoes resection of a well-differentiated neuroendocrine tumor after presenting with acute proptosis. An extensive clinical and radiographic evaluation reveals no other evidence of disease, establishing the diagnosis of a primary neuroendocrine tumor. The case presentation is followed by a brief review of the classification, presentation, and evaluation of orbital neuroendocrine tumors. Abstract : The authors report an exceedingly rare tumor—primary neuroendocrine tumor of the orbit—which presents with acute proptosis rather than progressive exophthalmos.